PENERAPAN AKUNTANSI FORENSIK DALAM MENGUNGKAP SKEMA FRAUD (STUDI FENOMENOLOGI KORUPSI HARVEY MOEIS) - Raffi Al Yasa Azhar; Agung Juliarto (Diponegoro Journal of Accounting, 2026)
According to data from the Association of Certified Fraud Examiners in 2016, corruption is the most common type of fraud in Indonesia. Corruption, on the other hand, is closely linked to financial statement manipulation. The Harvey Moeis corruption case is one that has significantly harmed Indonesia. Therefore, this case raises questions about the extent to which forensic accounting can be applied to uncover complex fraud schemes such as those involved in this case. This importance arises due to the approach of forensic accounting that allows auditors to evaluate documents, including transfer receipts, bank reconciliations, and financial statements. This study employed a qualitative research design with a phenomenological approach. The collected data were primary data through interviews with informants, as well as secondary data through literature study to support and contextualize the interpretation of the primary data. The collected data was then analyzed using thematic analysis.The research concludes, based on the informants, that Harvey Moeis committed corruption, fulfilling the legal elements stipulated in Article 2 of Law Number 31 of 1999 concerning the Eradication of Corruption, followed by a three-stage money laundering scheme: placement, layering, and integration. Based on the information provided by the informants, forensic accounting is considered to play a central role in the prosecution's investigation process in uncovering illicit financial flows, including tracing the movement of funds, analyzing financial transactions, conducting forensic data analysis, tracing assets, and applying Benford's Law to detect anomalies in financial statements. The investigative audit conducted by BPKP is also believed to constitute strong evidence in court in efforts to establish state losses allegedly resulting from the fraudulent acts committed by Harvey Moeis.